2003
DOI: 10.1074/jbc.m302512200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of HC-Pro, a Plant Virus Multifunctional Protein

Abstract: The helper component proteinase (HC-Pro) is a key protein encoded by plant viruses of the genus Potyvirus. HC-Pro is involved in different steps of the viral cycle, aphid transmission, replication, and virus cell-to-cell and systemic movement and is a suppressor of posttranscriptional gene silencing. Structural knowledge of HC-Pro is required to better understand its multiple functions. To this aim, we purified His-tagged wild-type HC-Pro and a N-terminal deletion mutant (⌬HC-Pro) from plants infected with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 44 publications
9
137
0
1
Order By: Relevance
“…Some of these miRNAs may get involved in virus-induced gene silencing. Helper component-proteinase (HC-Pro), p19, p21, and p69, are unrelated viral suppressors of gene silencing, and they play important roles in the virus response to plant antiviral silencing response (Plisson et al, 2003;Chapman et al, 2004). Several investigations demonstrated that several miRNAs are related the activity of these viral suppressors (Kasschau et al, 2003;Chapman et al, 2004;Chen et al, 2004;Llave, 2004).…”
Section: Functions Of Micrornas In Plantsmentioning
confidence: 99%
“…Some of these miRNAs may get involved in virus-induced gene silencing. Helper component-proteinase (HC-Pro), p19, p21, and p69, are unrelated viral suppressors of gene silencing, and they play important roles in the virus response to plant antiviral silencing response (Plisson et al, 2003;Chapman et al, 2004). Several investigations demonstrated that several miRNAs are related the activity of these viral suppressors (Kasschau et al, 2003;Chapman et al, 2004;Chen et al, 2004;Llave, 2004).…”
Section: Functions Of Micrornas In Plantsmentioning
confidence: 99%
“…In order to investigate which domain of HC-Pro is necessary for the interaction with ZmVDE, the coding sequences of each functional domain of HC-Pro reported by Plisson et al (2003;Fig. 4F) were constructed into pGBKT7 and then cotransformed with ZmVDEm into yeast cells.…”
Section: Scmv Infection Altered the Expression Levels Of Zmvdementioning
confidence: 99%
“…Dotted square in b represents arginine-rich region in 2b protein (Goto et al 2007). KITC, FRNK, IGN, CC/SC, C344 and H417 in c represent domains (single letter of amino acid and number of amino acids from N-terminal of HC-Pro) in HC-Pro (Plisson et al 2003). Asterisk shows CDNQLD domain, 12 amino acids downstream from FRNK (Desbiez et al 2010).…”
Section: Molecular and Biological Characterization Of Attenuated Virusesmentioning
confidence: 99%
“…In studies with HC-Pro mutants of Tobacco etch virus, hyposuppression of RNA silencing was correlated with milder virulence, but hypersuppression did not correlate with stronger virulence than with the wild type (TorresBarcelo et al 2008). HC-Pro is known as a multifunctional protein: aphid transmissibility, viral cell-to-cell and longdistance movement, viral amplification, symptom expression, synergism with other viruses, interaction with 20S proteasome and cysteine type proteolysis, siRNA binding and silencing suppressor including miR-guided cleavage of target mRNAs (Maia et al 1996;Plisson et al 2003;Shiboleth et al 2007). It is important to determine the structural requirements for RNA silencing suppressor activity, virus attenuation and cross protection.…”
Section: Potyvirusmentioning
confidence: 99%